2021
DOI: 10.3390/rs13051006
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the Research of the Effects of Etna Volcano Activity on the Features of the Ionospheric Total Electron Content Behaviour

Abstract: This research represents a contribution to the theory on the coupling of the volcanic activity and the ionospheric dynamics, represented by total electron content (TEC) patterns and their behaviour. The ionospheric response to the activity of the Etna volcano has been analysed using global navigation satellite system (GNSS)-derived TEC values, employing data from International GNSS Service (IGS) reference station near the volcano and on two distant IGS locations. Volcanic activity has been modelled using volca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Because of a more significant concentration of electrons, the ionosphere is a worldwide electric current, which is TEC (Total Electron Content, density of electrons in ionosphere). Many natural events, such as dust storms, thunderstorms [5], earthquakes, volcanic activity [6], radioactive gases [7], and solar radiation [8], induce variations in density of TEC. TEC rose during the previous high solar radiation cycle, which occurred in 2014 -2015; during this time, high-energy solar particles made contact with the earth's ionosphere, causing TEC to shift.…”
Section: Introductionmentioning
confidence: 99%
“…Because of a more significant concentration of electrons, the ionosphere is a worldwide electric current, which is TEC (Total Electron Content, density of electrons in ionosphere). Many natural events, such as dust storms, thunderstorms [5], earthquakes, volcanic activity [6], radioactive gases [7], and solar radiation [8], induce variations in density of TEC. TEC rose during the previous high solar radiation cycle, which occurred in 2014 -2015; during this time, high-energy solar particles made contact with the earth's ionosphere, causing TEC to shift.…”
Section: Introductionmentioning
confidence: 99%
“…As for the specific direction of volcano‐ionosphere coupling research, it has been established that there is a correlation between ionospheric and volcanic activity, with TEC variation as an effective diagnostic parameter (Aoyama et al., 2016; Cahyadi et al., 2021, 2020; Heki & Fujimoto, 2022; Li et al., 2016; J.‐W. Lin, 2017; X. Liu et al., 2017; Maletckii & Astafyeva, 2022; Manta et al., 2021; Pandara et al., 2021; Saito, 2022; Shults et al., 2016; I. Toman et al., 2021; Verhulst et al., 2022; S.‐R. Zhang et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the study of anomalous propagation characteristics in the ionosphere, a variety of information can be obtained, including the location of volcanic source, the scale of volcanic eruption, the height of plume, the rate of material ejection and the quality of ejection materials (Cahyadi et al., 2020; Li et al., 2016; Maletckii & Astafyeva, 2022; Shults et al., 2016; Watson et al., 2022). In the study of volcanic eruption activity cycles, it has been found that ionospheric anomalies can occur several days before the main eruption event (Li et al., 2016; Pandara et al., 2021; I. Toman et al., 2021). Particularly, the enhancement of TEC has been observed to occur during the main phase of volcanic eruption (I. Toman et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations